Urban Poor Community Settings’ Knowledge and Screening Practices for Cervical Cancer in Ibadan, Nigeria (2021)
PURPOSE This study investigated knowledge and screening practices for cervical cancer among two urban poor community settings in Ibadan, Nigeria. METHODS A cross-sectional design was used. ODK tool was used to collect quantitative data among a sample size of 500 respondents. Data were analyzed using IBM SPSS version 21 for descriptive and inferential statistics. Scores for knowledge were on a scale of 0-39 points (0-18 low, 19-23 fair, and 24-39 high knowledge). RESULTS A majority of respondents (77.2%) had low knowledge of cervical cancer and were not aware (93.6%) of the Papanicolaou test (Pap smear test) or cervical cancer screening (91.2%). Very few women (10%) were aware of the human papillomavirus vaccine for the prevention of cervical cancer, 4% had been screened with the Papanicolaou test, and one woman (0.3%) with visual inspection with acetic acid. Four (1.1%) women had taken human papillomavirus vaccine before. CONCLUSION The findings of this study have underscored a necessity for increased awareness creation through health promotion interventions and strategies to alleviate low knowledge, prevention, and screening practices for cervical cancer in poor community settings in Nigeria.